Blow out - Donaggio, Pino 1941- (<<The>> Criterion Coll., 2011)
Jack is a movie sound-effects man who believes he has accidentally recorded a political assassination. He enlists the help of Sally, a possible eyewitness to the crime who may be in danger herself, to uncover the truth. With its jolting stylistic flourishes, intricate plot, profoundly felt characterizations, and gritty evocation of early-1980s Philadelphia, this is an American paranoia thriller unlike any other, as well as a devilish reflection on the act of moviemaking
Bildformat 2.40:1, enhanced for 16:9 widescreen. - New, restored high-definition digital transfer
Orig.: USA, 1981
Enth. new hour-long video interview with De Palma, conducted by filmmaker Noah Baumbach ; new video interview with star Nancy Allen ; De Palma's 1967 feature "Murder à la Mod" ; new video interview with cameraman Garrett Brown on the Steadicam shots featured in the film within the film ; on set photos by Louis Goldman
Keywords: Verschwörung; Kriminalfilm; Toningenieur; Thriller; Mord; USA; Film